采用全联热-机械有限元模型计算盘式制动器尖叫声的预测工具 (A Predictive Tool to Evaluate Disk Brake Squeal Using A Fully Coupled Thermo--Mechanical Finite Element Model) - Hassan, Muhammad Zahir; Brosks, Peter C.; Barton, David C. (Shanghai Jiao Tong University of People’s Republic of China and Zahnradfabrik Friedrichshafen AG of Germany, 2013)

(untitled)
This paper presents a new integrated approach to the analysis of brake squeal modelling．It focuses on developing a validated thermo—mechanical finite element model by taking full account of the effect of thermal loading on the structural response of the brake．An integrated study involving time—dependent non—linear contact and a fully coupled transient thermal analysis are carried out to provide the contact and temperature distribution within the brake before executing an instability study using the complex eigenvalue technique．The results，in turn demonstrate the fugitive nature of brake squeal through the system eigenvalues that are extracted throughout the braking period. (摘要: 本文提出一个制动器尖叫模拟的新的综合方法, 它集中开发采用全考虑制动器结构响应热.负荷的影响的正确的热-机械有限元模型. 该综合研究包括实现与时间有关的非线性接触和全联.瞬态热分析, 在进行不稳定研究前, 采用复杂固有值技术, 提供在制动器内的接触和温度分布. 其结果依次通过制动全部系统固有值证实制动尖叫性质的变化.)